1989
DOI: 10.1139/v89-207
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of polar dienes with o-quinones

Abstract: The behaviour of various types of polar dienes towards halogenated ortho quinones has been investigated in a number of representative cases. As compared to the commonly used para analogues, o-quinones provide a wide range of products that indicate a keener response to the nature, number, and position of substituents on both reactants. 3-Halogenated-o-naphthoquinones 1 and 2 react smoothly with a representative vinologous ketene acetal 3, vinylketene acetals 4 and 5, and a monooxygenated diene 6 to provide vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, one class of potential dienophiles that has so far proven to be problematic are 3,4-unsubstituted 1,2-naphthoquinones . Indeed Fieser and Seligman observed that “1,2-naphthoquinone ... gives with dienes reaction mixtures of a most unpromising nature.” The challenge lies in finding conditions that promote cycloaddition without subsequent aromatization (Scheme ) . We report here on a solution to this problem through the use of Lewis acid catalysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, one class of potential dienophiles that has so far proven to be problematic are 3,4-unsubstituted 1,2-naphthoquinones . Indeed Fieser and Seligman observed that “1,2-naphthoquinone ... gives with dienes reaction mixtures of a most unpromising nature.” The challenge lies in finding conditions that promote cycloaddition without subsequent aromatization (Scheme ) . We report here on a solution to this problem through the use of Lewis acid catalysis.…”
mentioning
confidence: 99%
“…The adduct 3a was accessed for the first time (i.e. without aromatization to 4 ) in 99% yield (entry 1) . Addition of 1a to isoprene ( 2b ) also gave smooth conversion to adduct 3b (entry 2).…”
mentioning
confidence: 99%